(untitled) (Gaceta Técnica, 2024)
The objective of the study presented here is to optimize the mechanical support characteristics of resistant concrete used in road structures by applying coca leaf ash and steel fiber additives. Therefore, 45 specimens were used for compression resistance, another 45 as beams evaluated in bending, as well as 15 for settlement, in accordance with the provisions of standard E.0.60. On the twenty-eighth day, a maximum stress of 35,53 MPa in compression was achieved for the design made up of 1,75% coca leaf ash and 1,75% steel fibers, while in flexural strength a stress maximum of 5,24 MPa for design 2 made up of steel fibers and 2,50% coca leaf ash, the slump of design 1 made up of 1,75 of steel fiber and coca leaf ashes acquired a slump of 2,83”. The application of this mixture effectively contributes in a different magnitude to the properties evaluated in this study